Mechanism of superconductivity in K3C60. - Chen, G (1993)
Using electronic states and phonon states from the first-principles calculations and including both conventional electron-phonon charge coupling and Jahn-Teller coupling, we predict Tc and other superconducting properties. The only adjustable parameter in the theory is the screening length, Rsc. Using Rsc = 0.8-1.0 A, we find excellent agreement with experiment for Tc (16-18 K), pressure dependence of Tc (Delta Tc = -6 to -10 K for 1 GPa), and 12 C to 13 C isotope shift (alphaC = 0.2); experimental values: 19 K, -7 K, and 0.3, respectively.